Metodologi Studi Filsafat: Teologi Rasional Harun Nasution - Sri Suyanta; Sarah Ulfah (Tadabbur: Jurnal Peradaban Islam, 2022)
Among the developments in Islamic thought that are widely discussed is the science of kalam or theology. The science of kalam, or theology, has evolved rapidly over time, and many figures of Islamic thought, including Harun Nasution, have emerged. The purpose of this article is to learn about Harun Nasution's thought style and theology that he built. The research method used in this study is a qualitative method. The data collection technique used was descriptive library research. The results of this study indicate that Harun Nasution has three basic principles of a model of thinking in building his rational theology, namely: 1. the idea of progress; 2. coexistence between absolute-textual (qath'i) and relativifiably contextual (zhanni) areas; and 3. using a rational method of thinking. Meanwhile, Harun Nasution's foundation in the theology he built was reason and revelation. Harun Nasution's thoughts were heavily influenced by Mu'tazilah's rational theological thoughts. This is reinforced by the many writings of Harun Nasution, which discuss the thoughts of Muhammad Abduh, who is one of the Mu'tazilah figures.